EFEKTIVITAS BIMBINGAN ISLAMI DALAM MEMPROMOSIKAN KESEHATAN MENTAL - Mahdi Mahdi NK (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
The high number of people suffering from mental health disorders in the current era of globalization means that every individual must increase their understanding and awareness of the importance of mental health. Individuals who have mental health will make themselves able to develop their potential to be able to solve problems faced by their environment. In efforts to promote mental health for the community, Islamic counseling guidance is very influential in providing understanding and changing behavior regarding Mental Health, apart from health workers and medical personnel. Armed with the capacity and competence of service providers in the field of guidance and counseling, counselors or people who are experts in the field of counseling are pretty capable of promoting mental health; health promotion activities for the community through Islamic Guidance are considered quite effective. Islamic counseling is an effort to internalize Islamic teachings into aspects of people's lives. Apart from this activity being reinforced by religious arguments, its implementation is also carried out at religious moments. It is not uncommon for service providers to utilize technological information in all their preaching activities, and the results are pretty effective and efficient. Apart from being given information, people also feel educated so that a culture of clean and healthy living is embedded in the community based on religion and mental health in getting closer to Allah.